Globus pallidus/putamen T1WI signal intensity ratio in grading and predicting prognosis of neonatal acute bilirubin encephalopathy - Yi, Minggang; Lou, Jing; Cui, Ruodi; Zhao, Jianshe (Frontiers in Pediatrics, 2023)
This study sought to investigate the relationship between the globus pallidus/putamen T1WI signal intensity ratio (G/P ratio) and the acute bilirubin encephalopathy (ABE) in neonates, and to develop a new strategy for the grading and prognosis of ABE based on the G/P ratio.Methods A total of 77 full-term neonates with ABE were scored according to bilirubin-induced neurological dysfunction and divided into mild, moderate, and severe groups. Cranial magnetic resonance imaging (MRI) examinations were performed and the G/P ratio was recorded. The follow-up re-examinations were carried out at 6 months, 1 year, and 2 years after the initial examination. The neonates were then divided into two groups, the good prognosis group and the kernicterus spectrum disorder(KSD) group, according to the evaluation of Gesell Developmental Schedules and Brainstem Audio Electric Potential (BAEP) at 6 months.The differences of G/P ratios were statistically significant, not only among the mild, moderate, and severe ABE groups for the initial examinations, but also between the KSD and the good prognosis groups for the follow-up re-examinations. Therefore, the ABE grading model and prognosis predicting model could be established based on the G/P ratio. In the KSD group, the area under the receiver operating characteristic (ROC) curve of the G/P ratio-based predicting model was 93.5%, the optimal critical point was 1.29, the sensitivity was 88.2%, and the specificity was 93.3%. poor prognosis 删除[易]: . 删除[易]: poor prognosis 删除[易]: poor prognosis 删除[易]:Conclusions The G/P ratio can be used as an indicating parameter for both the clinical grading of neonatal ABE and the assessment of neonatal ABE prognosis. Specifically, the G/P ratio greater than 1.29 indicates a KSD of neonatal ABE.